SCHOOLS TO GROW IN: AN EVALUATION OF SECONDARY COLLEGES (Authors: Don Anderson, Marijke Salet, and Aat Vervoorn) - Harris, Justine (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1981)
Don Anderson, Marijke Salet, and Aat Vervoorn. SCHOOLS TO GROW IN: AN EVALUATION OF SECONDARY COLLEGES. Canberra: Australian National University Press, 1980. 162 pp.